Energy self-sufficiency in Northampton, Massachusetts (Hampshire Coll., Amherst, MA (USA), 1979)
The study is not an engineering analysis but begins the process of exploring the potential for conservation and local renewable-resource development in a specific community, Northampton, Massachusetts, with the social, institutional, and environmental factors in that community taken into account. Section I is an extensive executive summary of the full study, and Section II is a detailed examination of the potential for increased local energy self-sufficiency in Northampton, including current and future demand estimates, the possible role of conservation and renewable resources, and a discussion of the economic and social implications of alternative energy systems. (MOW)